Indicadores ambientais de sustentabilidade para uma instituição federal de ensino superior - Andréia Castro de Paula Nunes; Leci Martins Menezes Reis; Robson Garcia da Silva (Confins)
Discussions about sustainability have permeated daily life and, therefore, the academic sphere. In this context, Higher Education Institutions (HEIs) can play a key role in the application of sustainable practices. This study sought to select, from the perspective of specialists, environmental sustainability indicators for the Federal University of Rio Grande do Norte in the year 2015. For this purpose, based on bibliographical and documentary research, 110 environmental sustainability indicators were raised to the HEIs. Subsequently, repeated indicators were excluded and the remaining 50 were sent, through questionnaires, to 6 specialists to consider the level of relevance according to the Likert Scale. Among the universe of 50 indicators weighted by specialists, 6 obtained the highest simple arithmetic means of weights and, therefore, were considered the most relevant sustainability environmental indicators for the UFRN.